HUBUNGAN ADMINISTRATIF DENGAN KELOMPOK TANI DI KECAMATAN LANGOWAN TIMUR KABUPATEN MINAHASA - Debi ., Rapar; Welson M. Wangke; Celcius ., Talumingan (AGRI-SOSIOEKONOMI, 2017)
This research aims to know the relation of administration with farmer group class in East Langowan Subdistrict of Minahasa Regency. The study was conducted from April to July 2017. The data used were primary data obtained through the administrative examination of the activities and financial administration of each farmer group and direct interviews using questionnaires that were asked to the heads of farmer groups in East Langowan Sub District. Secondary data obtained directly from books, and articles. Data analysis used is descriptive analysis by using table. The Research results showed that the three classes of farmer groups in East Langowan Subdistrict of Minahasa Regency consisting of Beginner Class, Advanced Class and Middle Class, have no relationship with the administration of farmer groups in East Langowan District of Minahasa Regency. The better the administration of a farmer group does not mean that the farmer group should be at the highest grade level.